PARTISIPASI MASYARAKAT DALAM PEMBENTUKAN PERATURAN DAERAH - ARI YULIARTINI GRIADHI, NI MADE; SRI UTARI, ANAK AGUNG (Kertha Patrika; Vol 33 No 1 (2008)DO - 10.24843/KP.2008.v33.i01.p01)
The social participation is one of important thing that has to be considered in making the localgovernement regulation.In. Articel 53 of Act No. 10. 2004,about Making Governemen Regulation, the social partisipation has beenclearly regulated in -making governement regulation including local governement regulationSocial participation is one mode of political participation of the society in order to create good governance.So the Implementation of social participation in making governement regulation including local governementregulation has to be regulated more clearly.
Keywords: society participation, local government regulation, good governance